Influence of N₂ partial pressure on the microstructure, hardness, and thermal stability of CrZrSiN nanocomposite coatings - Kim, K.S.; Kim, H.K.; La, J.H.; Kim, K.B.; Lee, S.Y. (Сверхтвердые материалы, 2016)
The effects of N₂ partial pressure in the unbalanced magnetron sputtering process on the microstructure, hardness, and thermal stability of the CrZrSiN nanocomposite coating were investigated. A Досліджено вплив парціального тиску N₂ в процесі незбалансованого магнетронного розпилення на мікроструктуру, твердість і термостабільність нанокомпозитного покриття CrZrSiN. Исследовано влияние парциального давления N₂ в процессе несбалансированного магнетронного распыления на микроструктуру, твердость и термостабильность нанокомпозитного покрытия CrZrSiN. This research was supported by a grant from the Advanced Technology Center (ATC) Program funded by the Ministry of Trade, Industry& Energy of Korea.